Self-Regulated Learning Strategy in Online Speaking Class: How Is It Implemented? - Ratih Laily Nurjanah; Sri Waluyo; Salsa Billa Fauzia Tamami (Universitas Lancang Kuning, 2021)
This online learning era brings also challenges for both students and the lecturer side. This study aims to describe the learning activities conducted in an online learning speaking class based on Self-Regulated Learning strategy supported by online learning media. This is an ethnography study observing how the SRL is used in the classroom. The setting is a speaking class for 4th semester students at English Literature Department at Universitas Ngudi Waluyo. This study finds that describing learning objectives, giving models, recording a journal, sharing on a forum, and giving guidance for the next cycle of SRL are considered as some activities can be conducted to support the implementation of SRL in the classroom.